The powers, duties and control of persons participating in a compulsory winding-up of companies: some comparative aspects between the liquidation of a private company in South Africa and the "Gesellschaft mit beschraenkter Haftung" (Company with limited liability) in Germany - Gradel, Christian Georg (Department of Public Law, 2023)
This dissertation deals with the powers, duties, -and control of persons participating in a compulsory winding-up of a private company in South Africa and a "Gesellschaft mit beschraenkter Haftung" (Private company with limited liability) in Germany. At the outset it is therefore necessary to give a short description of the private company and to outline the different grounds for a winding-up in both countries, thereafter only the winding-up _grounds relating to insolvency will be discussed. Special emphasis will be placed on an explanation of the position of the liquidator and the "Konkursverwalter" (trustee in bankruptcy) in South African and German Law.